Long noncoding RNA LINC00152 promotes cell proliferation through competitively binding endogenous miR‐125b with MCL‐1 by regulating mitochondrial apoptosis pathways in ovarian cancer - Chen, Puxiang; Fang, Xiaolin; Xia, Bing; Zhao, Yan; Li, Qiaoyan; Wu, Xiaoying (Cancer medicine (Malden, MA), 2018)
Recently, an increasing number of studies have focused on the key function of long noncoding RNAs (lncRNAs) in biological activity. Abnormal lncRNA expression was found to relate to the development and pathogenesis of multiple cancers. LncRNA LINC00152 served as an oncogene in multiple cancers; however, its role in ovarian cancer remains unknown. In our research study, LINC00152 was upregulated in ovarian cancer tissues and cell lines. An increasing LINC00152 level was positively correlated with the histological grade, clinical stage, and poor prognosis of ovarian cancer patients. In addition, knockdown of LINC00152 reduced cell growth, induced cell apoptosis, and suppressed tumor growth. Moreover, we revealed that LINC00152 and Myeloid cell leukemia‐1 (MCL‐1) were targeted by miR‐125b and had the same miR‐125b combining site. The miR‐125b level was negatively correlated with the expression of LINC00152, while MCL‐1 was positively related to the LINC00152 level. MiR‐125b could affect LINC00152 levels as evaluated by qRT‐PCR. Finally, we affirmed that LINC00152 mediated cell proliferation by affecting MCL‐1 expression and MCL‐1‐mediated mitochondrial apoptosis pathways and by working as a competitive endogenous RNA (ceRNA) of miR‐125b. In summary, based on ceRNA theory, the combined research on miR‐125b and MCL‐1, and taking LINC00152 as a new study point, we provide new insight into the molecular mechanism of reversing cell proliferation in ovarian cancer. LINC00152 is upregulated in ovarian cancer tissues and cell lines. LINC00152 is a target of miR‐125b and modulates its target MCL‐1. LINC00152/miR‐125b/MCL‐1 axis modulated mitochondrial apoptosis pathway on cell apoptosis in ovarian cancer cells.